Strategi Komunikasi Kelompok Sadar Wisata (Pokdarwis) Dalam Meningkatkan Kunjungan Wisatawan Pada Destinasi Wisata Geopark Silokek - Nikken Herdiningsih; Ria Edlina (CV. ITTC INDONESIA, 2025)
Geopark Silokek is one of the potential assets to be developed in Sijunjung Regency which has natural beauty and uniqueness that will spoil the eyes of tourists. Silokek geopark has been designated as a national geopark in November 2018 and is in submission to UGG (unesco global geopark). silokek geopark tourist destinations are also included in the 50 best tourist villages inaugurated by menparekraf sandiaga uno, geopak silokek was also used as a rafting host in 2019 which was attended by 250 athletes from various countries, but silokek geopark tourist destinations are still not known by the wider community this is in accordance with data on the number of visitors in recent years. This research method is descriptive qualitative using the AIDDA theory by Wilbur Schramm to analyze the communication strategies used by tourism awareness groups in increasing tourist visits to silokek geopark tourist destinations. The results of this study are the communication strategy carried out by the Pokdarwis is to promote through social media TikTok and Instagram by creating content that shows the beauty and uniqueness of the Silokek Geopark, and Pokdarwis also holds various events that will attract tourist visits so that there is an increase in the number of tourists. The youth tourism and sports office of Sijunjung district has a special strategy to promote the Silokek geopark, namely by requiring all schools and government agency offices in Sijunjung district to wear the Silokek geopark logo to be better known by the wider community.